GENETIC DIFFERENTIATION IN POPULATIONS OF THE CORN LEAF APHID RHOPALOSIPHUM MAIDIS (FITCH) HEMIPTERA: APHIDIDAE - A. E. Timm,; L. K. Khalaf,; C. Michael Smith, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
The corn leaf aphid is a major pest causes damage to a range of cultivated crops. Little is known about the population genetics of the species. In this experiment, we examined the population genetic structure of the Rhopalosiphum maidis based on nucleotide sequencing of the cytochrome oxidase I (COI) gene and microsatellite analysis. Thirteen microsatellite markers developed for related aphid species were tested for use with R. maidis. Nine loci were found to amplify in R. maidis. Of these, seven were polymorphic. Nucleotide sequencing showed low variation, with one haplotype dominating in the regions sampled and four other haplotypes, differing by only a single base, occurring at a low frequency. Microsatellites confirmed low levels of diversity, but also showed moderate levels of population structure over local geographic scales, although this structure was not a result of isolation by distance. Over broader geographic scales, cluster analysis showed that populations from all U.S. states and China were almost indistinguishable and population assignment revealed that only 30% of individuals sampled could be correctly assigned to the population from which they were collected. Populations collected from Sorghum bicolor and Sorghum halepense could not be discriminated, indicating that S. halepense may act as a reservoir for the aphid during times when sorghum is not cultivated. The close similarity between individuals from China and the U.S. suggests that the lack of variation in the species may be explained by the parthenogenetic mode of reproduction, where males are seldom found.